2010
DOI: 10.1111/j.1863-2378.2009.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey on EquineCryptosporidiumandGiardiaInfections in Italy and Molecular Characterization of Isolates

Abstract: Cryptosporidium and Giardia are two of the most common enteric pathogens of domestic and wild animals and humans. However, little is known on the prevalence, clinical manifestations and economic and zoonotic significance of these infections in horses. This study was undertaken to investigate the prevalence, excretion patterns and risk factors related to the faecal shedding of Cryptosporidium oocysts and Giardia cysts in horses and the zoonotic potential of species/genotypes isolated. The survey was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 27 publications
4
49
0
1
Order By: Relevance
“…Cole et al (1998) reported diarrhea related to the presence of the above-mentioned protozoan, and Grinberg et al (2003) seemed to have evidenced this clinical sign in immunocompetent foals. In the present study, the consistency (p = 0.2119 and p = 0.2403) and color (p = 0.6842 and p = 0.5023) of feces were not associated with the occurrence of this disease in foals and mares, respectively, which agrees with the reports by Veronesi et al (2009) and Burton et al (2010).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Cole et al (1998) reported diarrhea related to the presence of the above-mentioned protozoan, and Grinberg et al (2003) seemed to have evidenced this clinical sign in immunocompetent foals. In the present study, the consistency (p = 0.2119 and p = 0.2403) and color (p = 0.6842 and p = 0.5023) of feces were not associated with the occurrence of this disease in foals and mares, respectively, which agrees with the reports by Veronesi et al (2009) and Burton et al (2010).…”
Section: Resultssupporting
confidence: 82%
“…Souza et al (2009) noted higher proportion of males naturally infected by Cryptosporidium spp. and concluded that the disease in equines, with different management types, is probably related to the immunological state and sanitary conditions found in the place where they live, since they were already considered sources of environmental infection (VERONESI et al, 2009). Concerning this aspect, it must be highlighted that, in previous epidemiological studies, Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations